Tiered Education and Training Systematic Offline and Online Mode Combination of PAUD teachers in North Sumatra Province - Tetty Muharmi (International Journal Reglement & Society (IJRS), 2022)
Education as a form of dynamic behavior change, both culture, civilization and community conditions. Education can accommodate changes that also occur in the era of the industrial revolution 4.0, globalization, the growth of the millennial generation, and national issues in the form of national civilization, national competitiveness, access to education, quality of education, vocational education and Indonesian employment, nationalism, radicalism, cultural/economic industries. creative, health, gender, demographic bonuses as challenges in the world of education. The social research method used is qualitative. The results showed that the method of education and training for PAUD teachers in the period after adapting to new normal learning or in adaptation after going through a pandemic period, began to be carried out by using virtual online training. The training method is carried out by learning using the Systematic Offline and Online Combination Mode Method in the context of career development through increasing the competency qualifications of PAUD teachers in the industrial era 4.0 the parties who are the institutions providing training for PAUD teachers. Education and training are expected to contribute to the realization of quality education for all Indonesian PAUD teachers.